Association between physical activity, sleep, and screen time and cardiometabolic risk factors among Brazilian adolescents: a cross-sectional analysis of a nationally representative sample - Silva, Diego A. S.; de Lima, Tiago R.; de Assis Guedes de Vasconcelos, Francisco; Bloch, Katia V.; Cureau, Felipe V.; Tremblay, Mark S. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background A prominent gap in the literature is the lack of evidence from low-middle-income countries on the association between adherence to 24-Hour Movement Guidelines (physical activity, sleep, and screen time) and cardiometabolic risk factors among adolescents. This study examined the association between adherence to the 24-Hour Movement Guidelines and cardiometabolic risk factors among Brazilian adolescents. Methods The probabilistic sample consisted of 29,226 adolescents (60.5% females) aged 12 to 17 years. This school-based cross-sectional study was conducted across all geographical regions of Brazil. Body mass and height were measured to estimate body mass index. Waist circumference, blood pressure, and venous blood samples were collected to estimate fasting glucose, triglycerides, and HDL cholesterol. Cardiometabolic risk factors were classified according to International Diabetes Federation criteria. Data on 24-hour movement behaviors (moderate- to vigorous-intensity physical activity, sleep duration, and recreational screen time) were collected using a self-administered questionnaire and classified according to the Canadian 24-Hour Movement Guidelines. Binary logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (95%CI). Results For males, lower ORs for high blood pressure [OR: 0.34 (95%CI: 0.20–0.58)], high triglycerides [OR: 0.47 (0.28–0.78)], metabolic syndrome [OR: 0.36 (0.17–0.78)], and the presence of two [OR: 0.49 (0.32–0.58)] and ≥ 3 cardiometabolic risk factors [OR: 0.35 (0.15–0.80)] were observed in adolescents who met the 24-Hour Movement Guidelines compared to peers who did not meet the guidelines. For females, no association was found between adherence to 24-Hour Movement Guidelines and cardiometabolic risks. Conclusion Meeting 24-Hour Movement Guidelines was beneficial for reducing the odds of cardiometabolic risk factors in males.